2018
DOI: 10.1186/s13017-018-0216-z
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-assisted closure (VAC®) systems and microbiological isolation of infected wounds

Abstract: BackgroundNegative pressure wound therapy is now largely used to treat infected wounds. The prevention and reduction of healthcare-associated infections is a high priority for any Department of Health and great efforts are spent to improve infection control systems. It is assumed that vacuum-assisted closure (VAC®) dressings should be watertight and that all the secretions are gathered in a single container but there is no consistent data on air leakage and possible dispersion of bacteria from the machine.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Some studies showed higher incidence in male patients, but some studies confirm higher incidence in female patients. In our sample of patients, 60% were males and 40% were females ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 74%
“…Some studies showed higher incidence in male patients, but some studies confirm higher incidence in female patients. In our sample of patients, 60% were males and 40% were females ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 74%
“…Contracción de la herida (macro deformación). Los efectos secundarios incluyen un aumento de la angiogénesis, formación de tejido de granulación y disminución del recuento bacteriano (14)(15). Este principio ha sido trasladado al manejo de las fugas anastomóticas del tracto digestivo superior e inferior que sean accesibles por vía endoscópica obteniendo cierres exitosos (16).…”
Section: Discussionunclassified
“…Yadav et al have found better results with NPWT in managing chronically infected wounds compared with conventional technique [12]. Cozza et al conducted a prospective experimental study including more than 10 patients and found that NPWT is not a risk factor for health care personnel associated with the management of infections [13]. Arundel et al in their randomized control study comparing NPWT with routine wound management found that healing of surgical wounds by secondary intention is very difficult.…”
Section: Discussionmentioning
confidence: 99%